Food Security in the Face of the COVID-19 Pandemic: The Simeulue Community's Strategies - Akmal Saputra; Nurkhalis Nurkhalis; Iwan Doa Sempena; Meg Jasadi Muaf; Nodi Marefanda (Jurnal Public Policy, 2022)
This article examines why and how the people of Simeulue realize food security during the COVID-19 pandemic. This research is important to reveal how the people of Simeulue can realize food security during the COVID-19 pandemic during a global community experiencing a crisis in various aspects. The author uses Max Weber's theory of social action to explain why the people of Simeulue have the motivation to achieve food security. In contrast, the Joined-up Government concept explains the synergy between stakeholders in realizing food security. This study uses qualitative research methods with data collection techniques through interviews with research informants. The study results indicate that the motivation for realizing food security for the Simeulue community is common. There are three social actions in realizing food security, namely traditional actions, value rationality actions and instrumental actions, while synergy between institutions is built through horizontal communication and coordination without elite domination by reproducing the local wisdom "Humasa Sebbel/Khumaha Heba" (planting rice at the same time).